Witchcraft in Venda: healing, violence and the symbolism of evil - Ravele, Dokotela Elias (Department of Religious Studies, 2026)
This thesis argues that witchcraft in Venda must be understood in relation to both traditional healing and traditional ways of symbolising evil. While outlining the basic Venda vocabulary of witchcraft, the thesis places that discourse about witches in the context of beliefs and practices relating to healing. As explored in detail in Chapter Three, knowledge about medicines provides a crucial background to the basic concept of witchcraft. Within the community, the healer or nanga is seen as the central figure. Without the protection provided by a =~ witches are believed to be able to operate freely in causing harm to persons and property. By virtue of his knowledge in healing, however, a == can be regarded as a witch. This irony introduces a certain ambiguity into the roles performed by traditional healers, sometimes blurring the line that divides good and evil applications of powerful medicines. The context of traditional healing, however, with its traditional medicines, roles, and techniques, provides the basic environment for identifying the harmful c~t::ct:; of witchcraft that are examined in detail in Chapter Four. Proceeding from healing to the symbolism of evil, the concluding chapter of the thesis, Chapter Five, examines the violence of witchcraft not only as a traditional way of identifying anti-social conduct but also as a modern symptom of economic competition and political rivalry.